Euler Type Integrals and Integrals in Terms of Extended Beta Function - Subuhi Khan; Mustafa Walid Al-Saad (Journal of Mathematics)
We derive the evaluations of certain integrals of Euler type involving generalized hypergeometric series. Further, we establish a theorem on extended beta function, which provides evaluation of certain integrals in terms of extended beta function and certain special polynomials. The possibility of extending some of the derived results to multivariable case is also investigated.